Legal Analysis of the Element of Premeditation in Article 340 of the Criminal Code Regarding Premeditated Murder (Case Study Of Decision Number: 907/PID.B/2020/PN MDN) - Widya Anisah; Khomaini Khomaini; Ramadhany Nasution (SEAN Institute, 2026)
This study aims to analyze the elements of criminal acts in Article 340 of the Criminal Code (KUHP) concerning premeditated murder proven in the primary indictment against the defendant Zuraida Hanum in the Medan District Court Decision Number: 907/Pid.B/2020/PN Mdn. In addition, this study also aims to determine the motives and factors that caused the defendant to commit premeditated murder. This study uses a normative juridical approach with a descriptive-analytical method, namely by examining secondary data in the form of legislation, legal literature, and related court decisions. Based on the results of the study, it was found that all elements in Article 340 of the Criminal Code, namely the elements of